Identification and Engineering of Transporters for Efficient Melatonin Production in Escherichia coli - Yang, Lei; Malla, Sailesh; Özdemir, Emre; Kim, Se Hyeuk; Lennen, Rebecca; Christensen, Hanne B.; Christensen, Ulla; Munro, Lachlan J.; Herrgård, Markus J.; Kell, Douglas B.; Palsson, Bernhard Ø. (Frontiers in Microbiology, 2022)
Transporter discovery and engineering play an important role in cell factory development. Decreasing the intracellular concentration of the product reduces production inhibition and/or toxicity. Lowering intracellular concentrations is especially beneficial for achieving a robust strain at high titers. However, the identification of transporters for xenobiotic chemicals in the host strain is challenging. Here we present a high-throughput workflow to discover E. coli transporters responsible for the efflux of the inhibitory xenobiotic compound melatonin. We took advantage of the Keio collection and screened about 400 transporter knock-outknockouts in the presence of a high concentration of melatonin. We found five transporters that when knocked out showed decreased tolerance to melatonin, indicating they are exporters of melatonin. We overexpressed these five genes individually in the production strain and found that one of them, yhjV, encoding a transporter with unknown substrates, resulted in a 27% titer increase in cultivation mimicking fed-batch fermentation. This study demonstrates how microbial cell factories can be improved through transporter identification and engineering. Further, these results lay the foundation for the scale-up of melatonin production in E. coli.